PENGARUH PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH TERHADAP TOTAL ASET PADA PT BANK PANIN SYARIAH TBK - Harahap, Aderina K (Universitas Malahayati, 2019)
This study aims to analyze the effect of mudharabah financing and musyarakah financing on totalassets at PT Bank Panin Syariah Tbk. The research method used in this study is quantitative researchand case study at PT Bank Panin Syariah Tbk. The type of data obtained from this study is secondarydata based on the results of quarterly financial statements of PT Bank Panin Syariah Tbk in 2015-2016. Source of data was obtained from the publication of PT Bank Panin Syariah Tbk and that wasaccessed from the official website https://www.paninbanksyariah.co.id/. The analysis tools used in thisstudy are normality test, multiple linear regression analysis, T test (partially), F test (simultaneously)and coefficient of determination (R2). The results showed that mudharabah financing did not affectthe total assets of PT Bank Panin Syariah Tbk, while musyarakah financing affects total assets of PTBank Panin Syariah Tbk partially. Simultaneously, mudharabah financing did not have effect andmusyarakah financing gives effect to total assets. Musharakah financing is one of the most dominantprofit sharing financing affecting total assets.Keywords: Mudharabah Financing, Musyarakah Financing, Total Assets.